2015
DOI: 10.3390/toxins7072586
|View full text |Cite
|
Sign up to set email alerts
|

Veal Calves Produce Less Antibodies against C. Perfringens Alpha Toxin Compared to Beef Calves

Abstract: Enterotoxaemia is a disease with a high associated mortality rate, affecting beef and veal calves worldwide, caused by C. perfringens alpha toxin and perfringolysin. A longitudinal study was conducted to determine the dynamics of antibodies against these toxins in 528 calves on 4 beef and 15 veal farms. The second study aimed to determine the effect of solid feed intake on the production of antibodies against alpha toxin and perfringolysin. The control group only received milk replacer, whereas in the test gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Similar to the inhibition of the alpha toxin activities, the ability of sera to neutralize the PFO activity was assessed by pre-incubating a two-fold dilution series of the sera (two wells per dilution) with a constant amount of perfringolysin O (2 μg/ml recombinant perfringolysin O). Recombinant perfringolysin O was produced as previously described [ 33 ]. The inhibitory capacity of the antiserum was expressed as the highest dilution that inhibited perfringolysin O induced hemolysis.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the inhibition of the alpha toxin activities, the ability of sera to neutralize the PFO activity was assessed by pre-incubating a two-fold dilution series of the sera (two wells per dilution) with a constant amount of perfringolysin O (2 μg/ml recombinant perfringolysin O). Recombinant perfringolysin O was produced as previously described [ 33 ]. The inhibitory capacity of the antiserum was expressed as the highest dilution that inhibited perfringolysin O induced hemolysis.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that milk replacer has an important predisposing effect in a ligated loop model for necro-haemorrhagic enteritis [ 35 ]. Furthermore, within the Belgian Blue breed, milk-fed veal calves produce less antibodies against C. perfringens alpha toxin than beef calves [ 36 ]. This suggests that calves fed cow’s milk or milk replacer might have less contact with alpha toxin, leading to the absence of active immunity, and thus potentially leaving the calves unprotected against necro-haemorrhagic enteritis.…”
Section: Epidemiologymentioning
confidence: 99%
“…This suggests that calves fed cow’s milk or milk replacer might have less contact with alpha toxin, leading to the absence of active immunity, and thus potentially leaving the calves unprotected against necro-haemorrhagic enteritis. Indeed, when C. perfringens is cultured in the presence of milk replacer, the alpha toxin activity of the supernatant decreases in a dose-dependent manner, compared to a negative control cultured without milk replacer [ 36 , Supplemental file 1]. The observation that contact with milk decreases toxin expression seems in contradiction to the observation that high milk diets predispose for necro-haemorrhagic enteritis.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation